Calidad de agua - Baeza, María Cecilia; Zamuner, Ester Cristina; Jaimes, Florencia; Herrera, Lorena Paola; Glessi, Walter; Puricelli, Marino Marcelo; Videla, Cecilia (3º Taller Manejo sustentable de Tierras en el Sudeste Bonaerense: Los Pinos, 2024)
Presentación en diapositivas